Pengaruh Motivasi terhadap Hasil Belajar Siswa Kelas V SDN se-Kelurahan Kelapa Lima - Elisabeth Aryanti Sanbein; Maxsel Koro; Martha K. Kota (Lembaga Yasin AlSys, 2025)
The importance of motivation in improving student learning outcomes serves as the primary background of this study, particularly for fifth-grade students at public elementary schools in the Kelapa Lima subdistrict. Learning motivation is viewed as an internal factor with a significant impact on students’ academic achievement. The objective of this study is to examine the effect of motivation on student learning outcomes. A quantitative method with a simple linear regression approach was employed. The sample consisted of 69 students, randomly selected from a population of 225 using a random sampling technique. Data were collected through questionnaires and analyzed statistically. The results show a positive and significant influence of motivation on learning outcomes, with a significance value of 0.000 (p < 0.05) and a coefficient of determination (R²) of 0.738, indicating that motivation contributes 73.8% to student learning outcomes. The study concludes that learning motivation has a significant effect on the academic achievement of fifth-grade students. The implication of these findings highlights the critical role of teachers and schools in fostering and developing student motivation to enhance the overall quality of learning.